KARAKTERISTIK PERAWAT PROFESIONAL YANG DIHARAPKAN MASYARAKAT UNTUK MENINGKATKAN KEPUASAN PASIEN RAWAT INAP - Ni Made Bela Utari; I Gusti Ayu Puja Astuti Dewi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
The quality of hospital services are highly influenced by the quality of services provided. The success of health services in improving services quality related with patient satisfaction. Based on several surveys, the results show that patient satisfaction is directly affected by the quality of services provided by hospital resources. In this case, the performance of health personnel particularly nurses. The aim of the study was to identify the characteristics of professional nurse expected by society to improve patient satisfaction in Sanjiwani General Hospital, Gianyar 2016. The research design was Descriptive-Cross Sectional. This study involved 250 respondents with Non-Probability Sampling technique (Purposive Sampling). Data were collected by questionnaire and analyzed by using SPSS 17. Findings of this study found that the highest percentage was in sub-variable of professional nurse characteristic based on ability to provide certain services (53.6% or 134 respondents) and the lowest percentage was in the sub-variable of professional nurse characteristic based on ability to have the autonomy to make decisions and to do nursing care (16.4% or 41 respondents). In conclusion, nurses as health care providers should possess professional nurse characteristics, especially the ability to provide humanistic health care with holistic approach. This may improve patient satisfaction as a recipient of health care services. Keywords: characteristics of professional nurses, satisfaction, society